Weight suppression and risk of future increases in body mass: effects of suppressed resting metabolic rate and energy expenditure(1)(2)(3) - Stice, Eric (American Society for Nutrition, 2011)
Background: Weight suppression, which reflects the difference between the highest previous weight and current weight, has predicted future increases in body mass index (BMI) and bulimic pathology; however, the mechanisms underlying these predictive effects are unclear. Objective: The current study sought to test whether weight suppression predicts future increases in BMI and bulimic symptoms and whether suppressed resting metabolic rate (RMR) and suppressed total energy expenditure (TEE) drive these relations. Design: A randomly selected subsample of 91 young women in their first year of college with body image concerns completed an RMR assessment—a doubly labeled water assessment of TEE—and provided data on weight suppression and change in BMI and bulimic symptoms over a 6-mo follow-up period. Results: Weight suppression predicted future increases in BMI and correlated inversely with suppressed RMR and TEE, yet this predictive effect did not decrease when suppressed RMR and TEE were controlled for. Weight suppression, however, did not predict future increases in bulimic symptoms. Conclusions: The results provide additional evidence that weight suppression predicts future increases in BMI but not in bulimic symptoms. Weight suppression showed moderate relations with suppressed RMR and TEE, but these variables do not appear to drive the predictive effect on future increases in BMI. This trial was registered at clinicaltrials.gov as NCT00433680.